Abordagens de ensino de gramática em exercícios morfológicos e morfossintáticos de gramáticas didáticas da Língua Portuguesa para os Anos Finais do Ensino Fundamental e para o Ensino Médio - Souza, Francisco Elton Martins de (2019)
The main objective of this research was to investigate the approaches of grammar teaching in morphological and morphosyntactic exercises of didactic grammars of the Portuguese Language for Elementary School - Final Years and for High School. In order to situate our work in the vast field of Applied Linguistics, we take into account the considerations present in Celani (2000), Almeida Filho (2011) and Lopes (2011). In order to locate our research in time and space, we traced a historical picture about the emergence of didactic material in the world and in Brazil, as well as a historical panorama of grammar studies, with its current implications for the teaching of mother tongue. With regard to grammar teaching approaches, we focus on the basic work of Halliday, McIntosh and Strevens (1974), which has, in Brazil, countless followers, such as Possenti (1996), Neves (2002, 2010, 2012, 2013 ), Antunes (2003 and 2007), Jurado & Rojo (2006), Travaglia (2009, 2011 and 2013), Martelotta (2010). We also outline the postulate regarding the practice of linguistic analysis, based on authors such as Geraldi (1997), Franchi (2006) and Bezerra and Reinaldo (2013). Our research was qualitative-explanatory and had as a method of approach the induction, since the analysis of the data allowed us to perceive that the grammar teaching approaches follow trends that are repeated in the most diverse didactic materials, as well as in the several chapters of a same textbook. The research allowed to conclude that the approaches – descriptive, prescriptive and productive – are not inherent in grammar teaching in Elementary School - Final Years or High School, with authors turning to all approaches, or one of them, regardless of level / year for which your material is directed. The research also revealed that each author presents the predominance of at least one approach or a balance between the three approaches, and that this predominance/balance changes from author to author. Our thesis is that what is recommended is the balance between grammar teaching approaches, since each type of teaching contributes, in its own way, to the teaching-learning process of the mother tongue